2023
DOI: 10.1289/ehp12016
|View full text |Cite
|
Sign up to set email alerts
|

Mixtures of Metals and Micronutrients in Early Pregnancy and Cognition in Early and Mid-Childhood: Findings from the Project Viva Cohort

Abstract: Background: The developing fetal brain is sensitive to many environmental exposures. However, the independent and joint effects of prenatal exposure to metals and micronutrients on child cognition are not well understood. Objectives: Our aim was to evaluate associations of first-trimester ( wk) maternal erythrocyte concentrations of mixtures of nonessential and essential metals and micronutrients with early ( y) and mid-childhood ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…However, available second-trimester maternal trimester Hg and Pb indicated consistent exposure to these metals during pregnancy (rSpearman = 0.61-0.65; p < 0.001; data not shown). Metal concentrations in erythrocytes have also been measured in a subset of children in Project Viva in early childhood (N = 349; mean = 3.2 years of age) [78]. As previously reported, median early childhood concentrations of Zn and most non-essential metals were lower than maternal firsttrimester concentrations.…”
Section: Discussionmentioning
confidence: 68%
“…However, available second-trimester maternal trimester Hg and Pb indicated consistent exposure to these metals during pregnancy (rSpearman = 0.61-0.65; p < 0.001; data not shown). Metal concentrations in erythrocytes have also been measured in a subset of children in Project Viva in early childhood (N = 349; mean = 3.2 years of age) [78]. As previously reported, median early childhood concentrations of Zn and most non-essential metals were lower than maternal firsttrimester concentrations.…”
Section: Discussionmentioning
confidence: 68%
“…The intake status of B vitamins, folic acid, vitamin B12, vitamin B6, and riboflavin may all affect the overall status of choline, which can have a direct impact on fetal neurodevelopment, both prenatally and postnatally, and may also have an effect on methylmercury toxicity [48]. Studies have shown that intake of folic acid and vitamin B12 during pregnancy can help prevent neural tube defects [49]. Our study highlighted that eating food groups containing both proteins and micronutrients throughout the pregnancy benefits the offspring's neurodevelopmental behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In the current issue of Environmental Health Perspectives , Thilakaratne et al. 7 take on this challenge in their study of prenatal environmental exposures and cognitive outcomes in early and mid-childhood. The authors defined a “toxic” mixture of six nonessential metals, including the classic neurotoxicants lead, mercury, and arsenic, and a “nutrient” mixture of five essential metals and two micronutrients, folate and vitamin B12.…”
mentioning
confidence: 99%